A review of factors affecting the transfer of sexual and reproductive health training into practice in low and lower-middle income country humanitarian settings - Beek, Kristen (Confl Health, 2017)
BACKGROUND: A lack of access to sexual and reproductive health (SRH) care is the leading cause of morbidity and mortality among displaced women and girls of reproductive age. Efforts to address this public health emergency in humanitarian settings have included the widespread delivery of training programmes to address gaps in health worker capacity for SRH. There remains a lack of data on the factors which may affect the ability of health workers to apply SRH knowledge and skills gained through training programmes in humanitarian contexts. METHODS: We searched four electronic databases and ten key organizations’ websites to locate literature on SRH training for humanitarian settings in low and lower-middle income countries. Papers were examined using content analysis to identify factors which contribute to health workers’ capacity to transfer SRH knowledge, skills and attitudes learned in training into practice in humanitarian settings. RESULTS: Seven studies were included in this review. Six research papers focused on the response stage of humanitarian crises and five papers featured the disaster context of conflict. A range of SRH components were addressed including maternal, newborn health and sexual violence. The review identified factors, including appropriate resourcing, organisational support and confidence in health care workers that were found to facilitate the transfer of learning. The findings suggest the presence of factors that moderate the transfer of training at the individual, training, organisational, socio-cultural, political and health system levels. CONCLUSION: Supportive strategies are necessary to best assist trainees to apply newly acquired knowledge and skills in their work settings. These interventions must address factors that moderate the success of learning transfer. Findings from this review suggest that these are related to the individual trainee, the training program itself and the workplace as well as the broader environmental context. Organisations which provide SRH training for humanitarian emergencies should work to identify the system of moderating factors that affect training transfer in their setting and employ evidence-based strategies to ameliorate these.